2002
DOI: 10.1007/s00415-002-0885-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cognitive level and depression severity are different in patients with left and right hemispheric stroke within the first year of illness

Abstract: Causes of cognitive impairment after stroke are not yet clear because a large number of sociodemographic and clinical variables complicate the understanding of the phenomenon. We aim to evaluate sociodemographic and clinical predictors of cognitive level and depression in subjects with different lesion laterality. We assessed 153 right (n = 87) and left (n = 66) unilateral first-ever stroke patients within the first year of illness with the Structured Clinical Interview for DSM-IV-Patient Edition, the Hamilton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
3
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 47 publications
5
32
3
4
Order By: Relevance
“…Furthermore, PET studies during migraine attacks demonstrated episodic dysfunction of certain brainstem areas [20]. Our data are consistent with these reports and with previous studies showing a relationship between anxiety and depression with vascular left cerebral lesions [4] and with metabolic alteration in left frontal regions [5]. Therefore, the correlation between left unilateral migraine, anxiety and depression we found in migraineurs offers new clues on the role of left cerebral hemisphere in these disorders.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, PET studies during migraine attacks demonstrated episodic dysfunction of certain brainstem areas [20]. Our data are consistent with these reports and with previous studies showing a relationship between anxiety and depression with vascular left cerebral lesions [4] and with metabolic alteration in left frontal regions [5]. Therefore, the correlation between left unilateral migraine, anxiety and depression we found in migraineurs offers new clues on the role of left cerebral hemisphere in these disorders.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, two vascular risk factors emerged as independent predictors of DS, namely pre-existent TIA(s) and a history of diabetes mellitus (either type 1 or type 2). The finding that diabetes mellitus is a risk factor for the presence of depressive pathology after stroke has been reported before, but this association was found solely in patients with a stroke in the left hemisphere [8]. According to some authors, diabetes is a risk factor for DS through a biological mechanism linking the metabolic changes of diabetes to changes in the brain structure or function [41].…”
Section: Gms Nys Et Al / Journal Of the Neurological Sciences XX mentioning
confidence: 89%
“…In the Spalletta et al study, 25 among 153 patients with first-ever stroke lesions of the left (n = 87) or right (n = 66) hemisphere who were less than 1-year poststroke, patients with lefthemisphere lesions and major depression (n = 30) showed significantly more impairment on the MMSE than nondepressed patients with left-hemisphere lesions (n = 27).…”
Section: Diagnosismentioning
confidence: 97%